Isolation and Identification of Fungi from Wounds and Burns of Human and Farm Animals - AL-Tameemi, Hayder Abd Ali Neamah; Khalaf, Jenan Mahmood (The Iraqi Journal of Veterinary Medicine, 2013)
This study was conducted to isolate and identify the fungi that infect burn wounds in humans and acquired wounds or wounds resulted from surgical operation in farm animals. A total of 110 cotton swabs, 60 cotton swabs were collected from wounds to 6 kinds of farm animals, which include 10 swabs for each type of these animals (cattle, sheep, goats, cats, dogs, donkeys). As well as 50 swabs were collected from human burns. All these samples were cultured onto Sabouraud dextrose agar (oxoid, England) to detect fungi in wounds of humans and animals in Baghdad city.Identification of Yeasts were done by use RapID™ Yeast Plus System (remel, USA), While the Identification ofmoulds were done in the Central Public Health Laboratory, depending on the macroscopic appearance of the colony and microscopic examination. Growth was positive for 49 (81.66%) cases of the total 60 wounds swabs. Which detect etiological fungi that infect wounds of animals were as follows:Trichosporon beigelii 6 (10%), Candida parapsilosis 2 (3.33%), Yarrowia lipolytica 1 (1.66%), prototheca zopfii 1 (1.66%), Candida lambica 1 (1.66%), Aspergillus flavus 7 ( 11.66%), Penicillum 6 (10%), Rhizopus 6 (10%) , Aspergillus niger 5 ( 8.33%), Trichophyton rubrum 5 (8.33%), Mucor5 (8.33%), Alternaria 4 (6.66%), Aspergillus fumigates 2 (3.33%), Aspergillus terrus 2 (3.33%), Epidermophyton floccosum 2 (3.33%) , Helminthosporium 1 (1.66%), Geotricum 1 (1.66%), Fusarium 1 (1.66%). As well as the growth was positive for 37 (74%) cases of 50 swabs taken from the burns in humans. They were found that the causative agent of burns wounds in humans were:Candida albicans 3 (6%), Yarrowia lipolytica 2 (4%), Trichosporon beigelii 1 (2%), Cryptococcus albidus 1 (2%), Prototheca zopfii 1 (2%), Candida guilliermondii 1 (2%), Aspergillus niger 6 (12%), Aspergillus flavus 4 (8%), Aspergillus fumigates 3 (6%), Penicillum 5 (10%), Rhizopus 3 (6%), Alternaria 2(4%), Fusarium 1 (2%), Trichophyton rubrum 1 (2%), Mucor 1 (2%), Helminthosporium 1 (2%), Geotrichum 1 (2%). Drug susceptibility test was done by using disc diffusion method onto Muller Hinton agar, in this study use 5 types of antifungal disc were used(Amphotrecin B, Nystatin, Fluconazole, Ketoconazole, Itraconazole).